Comparison of StudRetentor Versus Bar-Clip Attachment as ImplantSupported Systems Used in Overdentures: A Systematic Review and Meta-Analysis. Issue 3 (2022) - Castro, Filipe Miguel Correia de; Martins, Gustavo Z.; Oliveira, Hélder Filipe P. de; Hernández, Pablo B.; Gavinha, Sandra; Fernandes, Gustavo V. O.
No abstract available